Sea urchins (traditional design) - De la Ossa, Marianna, artist (Colorado State University. Libraries, 1998)
A blouse made and worn by Marianna de la Ossa.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton, synthetics.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama